CULTIVATING RESILIENT CAPACITY AND EXPANSION STRATEGIES: EVIDENCE FROM MANUFACTURING FIRMS IN RIVERS STATE - Dr. Macaulay Enyindah Wegwu (Scholar Express Journal, 2025)
This study critically investigated the relationship between resilient capacity and expansion strategies of manufacturing firms in Rivers State. The crux of the problem is that it has been asserted by practitioners and management researchers that management of manufacturing firms have failed to develop the ability to create resilience culture involving employing people who should be well-chosen, inspired, guided that can foresee significant developing patterns and trends, overcome nearly all challenges and disturbances that will enable them to continuously achieve expansion objectives. This assertion thus gave rise to this study which has explored the dimensions of resilience capacity that will enable them achieve expansion objectives. As a consequence, the aim of the research was explored, four research objectives were advanced that formed the basis for the research, four research questions were also advanced, and four research hypotheses were formulated in their null forms to enable the realization of the study’s aim and objectives. The cross sectional survey which is a type of the quasi experimental design was used in this study, because the variables were not under the control of the researcher. A total number of 95 respondents occupying managerial positions in the 10 registered food and beverage firms constituted the population for the study. Data was collected using questionnaire, and a total of 81copies of the questionnaire which represented 85% of questionnaire distributed was successfully retrieved and used for the study. The data collected was analyzed using the Pearson Product Moment Correlation statistical analysis. As a result of the analysis, findings revealed a significant relationship between the dimensions of resilient capacity (response and adaptive capacity) and the measures of expansion strategies (internal and external). It was thus, concluded that an organisation’s resilient capacity contributes to firm’s expansion, and thus has linear relationship. The study among others recommended that the management of the manufacturing firms should develop resilient capacity that will inculcate the development of expansion strategies in turbulent environment in order to achieve their expansion objectives
Keywords: Resilient capacity; Responds; Adaptive capacity